PENGARUH PERTUMBUHAN AKTIVA PRODUKTIF, DANA PIHAK KETIGA, TINGKAT KREDIT BERMASALAH DAN UKURAN LPD PADA KINERJA OPERASIONAL - Setyawati, Anak Agung Putu; Suartana, I Wayan (E-Jurnal Akuntansi, 2014)
This study aims to determine the effect of growth in earning assets, third-party funds, the level of non-performing loans and the size of the operational performance of LPD LPD in Denpasar. The samples in this study were 30 LPD in Denpasar obtained with saturated sampling method and tested using the partial regression test (t-test). After analyzing the results showed that all independent variables partially consisting of growth assets, third-party funds, the level of non-performing loans and the size effect on the operational performance of LPD LPD in Denpasar Year 2008-2012. Partial test showed that the growth of third-party funds (savings and time deposits) and the level of non-performing loans ratio has a positive effect on ROA in LPD Denpasar, while the growth in earning assets and the size of the negative effect on the ratio LPD LPD BOPO in Denpasar Year 2008-2012 with the level of 95% confidence.
Keywords: Assets, Third Party Funds, level of Non Performing Loans, ROA ratio